E-Marketing in Accommodation Business Model Innovation at Airbnb in Bali - I Nyoman Mokoh Wijaya; I Made Darma Oka; Ni Gst Nym Suci Murni; Putu Widya Darmayanti (Institut Pariwisata dan Bisnis Internasional, 2023)
In conducting tourism business activities, the internet is one form of utilizing information technology in the era of globalization. The intensity of internet use also has a very large influence on changes that occur in the concept of business utilization, especially in the marketing business model that is carried out. Competition in the era of globalization requires companies that provide goods or services to always be responsive and observant in what is happening today. Airbnb is an online media that brings together tourism accommodation service providers and managers with tourism accommodation service users in the form of a website that can be accessed via mobile phones. This study analyzes the implementation of e-marketing in the accommodation business model innovation on Airbnb sites in Bali. Data was collected through observation, in-depth interviews and literature study. Data analysis was descriptive qualitative using Porter's Five Force Models (PFFM). This model is used to analyze competitive forces in marketing accommodation in Bali through the airbnb website. The results showed that the implementation of e-marketing in the innovation of the tourism accommodation business model on the Airbnb site in Bali by applying the PFFM proved to be quite effective. The competitive advantages of the Airbnb site are: multiple listings, two booking process confirmation systems, smaller booking commissions, competitive prices, no disparity rates, ease of registration, and marketing unique accommodation titles. Implementation of Porter's model is used to increase accommodation unit revenue by accepting bookings on the Airbnb situs site.